Effectiveness of Restaurant Waiter Communication at Resinda Hotel Karawang - Dara Siska Aulia; Tito Pandu Raharjo; Siti Zakiah (STKIP Singkawang, 2023)
Good service can be seen from the effective communication that exists between service providers and guests. A waiter becomes a very important factor in the process of communication and service. One area that is the centre of service is in the area of The Oryza Restaurant. However, it was found that there was a communication gap that led to miscommunication and erroneous information capture. Often communication gaps arise when waiters deal with foreign tourists. One of the factors causing this gap is the language skills of the waiter. This study aimed to analyze the communication gap to measure the effectiveness of service communication at The Oryza Restaurant and the quality of a waiter as a communicator. This study used a descriptive qualitative method with data collection through interviews and observation as well as document study support. Data processing was carried out using coding techniques and data triangulation from interviews and observations. The results of the study showed that there is a gap in communication due to the language factor which causes the ineffectiveness of two indicators in effective communication, namely Content and Clarity. Then it was also found that the waiter as a communicator is capable of ethos and attitude in serving guests. With this research, it is hoped that there will be a periodic evaluation and control process for each service worker to get quality waiters who are qualified to serve and comply with company service standards.